Folding and functionalizing DNA origami: a versatile approach using a reactive polyamine - Postigo, Alejandro; Marcuello, Carlos; Verstraeten, William; Sarasa, Santiago; Walther, Tobias; Lostao, Anabel; Göpfrich, Kerstin; del Barrio, Jesús; Hernández-Ainsa, Silvia (Journal of the American Chemical Society, 2025)
DNA nanotechnology is a powerful synthetic approach to crafting diverse nanostructures through self-assembly. Chemical decoration of such nanostructures is often required to tailor their properties for specific applications. In this Letter, we introduce a pioneering method to direct the assembly and enable the functionalization of DNA nanostructures using an azide-bearing functional polyamine. We first demonstrate the successful polyamine-assisted folding of a scaffolded DNA origami nanostructure equipped with reactive azide groups. Leveraging this reactivity, we next showcase the decoration of the DNA origami via strain-promoted azide-alkyne cycloaddition with dibenzocyclooctyne-containing functional molecules. Specifically, we incorporate a fluorophore (Cy5), polyethylene glycol (PEG), and a hydrophobic phosphatidylethanolamine (PE) tag to tailor the properties of our DNA origami nanostructures. Our approach is expected to streamline and reduce the cost of chemical customization of intricate DNA nanostructures, paving the way for enhanced versatility and applicability.